Positive Predictive Value of Dried Blood Sampling of TSH in Diagnosing Congenital Hypothyroidism in Neonates Born at a Tertiary Care Hospital: PPV of Dried Blood Sampling of TSH in Diagnosing Congenital Hypothyroidism - Khan, Wasif Ahmed; Naz, Fizzah; Arif, Muzna; Khan, Shahiryar; Majid, Hafsa; Nisar, Imran; Humayun, Khadija Nuzhat (Pakistan Journal of Health Sciences, 2026)
Congenital hypothyroidism (CH) is one of the most common preventable causes of intellectual disability in children. Early detection through newborn screening is essential for timely intervention. However, the predictive accuracy of DBS-TSH varies across populations, and limited local data are available from Pakistan. Objectives: To determine the positive predictive value (PPV) of dried blood samples of thyroid-stimulating hormone (DBS-TSH) in diagnosing congenital hypothyroidism (CH) in neonates. Methods: This retrospective cohort study using screening registry data was conducted at the newborn screening program, Aga Khan University Hospital, Karachi, from March 2023 to March 2024. Records of neonates screened from April 2019 to December 2022 were reviewed. Neonates with DBS-TSH >10 mIU/L were labeled screen-positive and underwent confirmatory testing with serum TSH and free T4 within two weeks. Neonates with Serum TSH (>20 mIU/L) were considered true positive for congenital hypothyroidism. Results: Of 30,402 neonates screened, 538 (1.76%) were screen positive. Mean DBS-TSH was 16.1 ± 12.6 mIU/L. Among them, 478 (88.8%) had 10–20 mIU/L (Group 1), and 60 (11.2%) had >20 mIU/L (Group 2). Confirmatory testing was available for 385 infants, of whom 33 were true cases of CH, yielding a PPV of 8.57% (95% CI: 5.9%–11.7%). Higher PPV was observed when sampling occurred at >48 hours. A DBS-TSH cutoff ≥35 mIU/L showed PPV of 95% (95% CI: 76.18 – 99.88), which may justify early treatment consideration. Conclusions: DBS-TSH screening at a cutoff of >10 mIU/L yields modest PPV for CH. Higher DBS-TSH values and appropriate sampling time significantly enhance predictive accuracy.